RAGE and Soluble RAGE: Potential Therapeutic Targets for Cardiovascular Diseases - Koyama, Hidenori (ScholarOne, 2007)
Receptor for advanced glycation end-products (RAGE) is known to be involved in microvascular complications in diabetes. RAGE is also profoundly associated with macrovascular complications in diabetes through regulation of atherogenesis, angiogenic response, vascular injury, and inflammatory response. The potential significance of RAGE in the pathogenesis of cardiovascular disease appears not to be confined solely to nondiabetic rather than diabetic conditions. Numerous truncated forms of RAGE have recently been described, and the C-terminally truncated soluble form of RAGE has received much attention. Soluble RAGE consists of several forms, including endogenous secretory RAGE (esRAGE), which is a spliced variant of RAGE, and a shedded form derived from cell-surface RAGE. These heterogeneous forms of soluble RAGE, which carry all of the extracellular domains but are devoid of the transmembrane and intracytoplasmic domains, bind ligands including AGEs and can antagonize RAGE signaling in vitro and in vivo. ELISA systems have been developed to measure plasma esRAGE and total soluble RAGE, and the pathophysiological roles of soluble RAGE have begun to be unveiled clinically. In this review, we summarize recent findings regarding pathophysiological roles in cardiovascular disease of RAGE and soluble RAGE and discuss their potential usefulness as therapeutic targets and biomarkers for the disease.